1999
DOI: 10.1002/(sici)1097-4628(19991128)74:9<2220::aid-app11>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyvinylpyrrolidone molecular weights on morphology, oil/water separation, mechanical and thermal properties of polyetherimide/polyvinylpyrrolidone hollow fiber membranes

Abstract: ABSTRACT:We prepared polyetherimide (PEI) hollow fiber membranes using polyvinylpyrrolidones (PVP) with different molecular weights (PVP 10,000, PVP 40,000, and PVP 1,300,000) as additives for oil/water separation. Asymmetric hollow fiber membranes were fabricated by wet phase inversion technique from 25 wt % or 30 wt % solids of 20 : 5 : 75 or 20 : 10 : 70 (weight ratio) PEI/PVP/N-metyl-2-pyrrolidone (NMP) solutions and a 95 : 5 NMP/water solution was used as bore fluid to eliminate resistance on the internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…This could be attributed to the reaction between hypochlorite and PVP that caused chain scission of PVP molecules and the eventual leaching of PVP from the membrane matrix [8], which was subsequently confirmed by the SEM images. The results in this study were also in agreement with the previous work [10][11][12]. Table 3 also indicates that there were no significant changes in both pure water flux and retention of the membranes treated under different concentrations of 500 and 1000 mg l −1 , which suggested that there was an optimum hypochlorite concentration around 500 mg l −1 for the treatment to achieve a high flux PAN membrane.…”
Section: Effect Of Hypochlorite Treatmentsupporting
confidence: 91%
See 2 more Smart Citations
“…This could be attributed to the reaction between hypochlorite and PVP that caused chain scission of PVP molecules and the eventual leaching of PVP from the membrane matrix [8], which was subsequently confirmed by the SEM images. The results in this study were also in agreement with the previous work [10][11][12]. Table 3 also indicates that there were no significant changes in both pure water flux and retention of the membranes treated under different concentrations of 500 and 1000 mg l −1 , which suggested that there was an optimum hypochlorite concentration around 500 mg l −1 for the treatment to achieve a high flux PAN membrane.…”
Section: Effect Of Hypochlorite Treatmentsupporting
confidence: 91%
“…1a and b reveal that the cross-section of the as-spun fiber had a finger-like structure going through from the inside to the outer side of the fiber. This indicates that the addition of 3% PVP 360K in the dope solution was not enough to suppress macrovoids, which was in agreement with [10]. Fig.…”
Section: Morphology Of Membranessupporting
confidence: 81%
See 1 more Smart Citation
“…The enhancement in membrane hydrophilicity could be related to the presence of the hydrophilic PVP into the polymeric matrix and not washed away during membrane post-treatment with water [29][30][31]. The water permeability is reported in Table 2.…”
Section: Membrane Characterizationmentioning
confidence: 99%
“…However, the addition of PVP with high molecular mass results in a low flux membrane due to swelling of the residual PVP at the surface of pore walls when water passes through the membrane pores [14]. Therefore, hypochlorite treatment has been applied to increase flux of MF/UF membranes made from a blend of PVP and hydrophobic polymers [14][15][16][17]. Recently, the authors [18,19] have investigated hypochlorite treatment over different time and different concentrations to achieve high flux membranes spun from blends of CA and PVP.…”
Section: Introductionmentioning
confidence: 99%